SOSIALISASI FLUIDA PEMBORAN: PENGANTAR KOMPREHENSIF UNTUK LABORAN DAN GURU SMK MIGAS CIBINONG, JAWA BARAT - Samura, Lisa; Pearlo, Kevin Lukas; Soekardy, Mentari Gracia; Hidayat, Hifdzan Rizki; Burhannudinnur, Muhammad; Prakoso, Suryo; Rosyidan, Cahaya; Maulani, Mustamina; Satiyawira, Bayu; Djumantara, Maman (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
The world of oil cannot be separated from drilling operations in extracting hydrocarbons from below the earth's surface. Drilling mud or drilling fluid is essential to the drilling process. Cibinong Oil and Gas Vocational School is a vocational school that has two study programs, namely, Oil and Gas Drilling Engineering and Oil and Gas Production Engineering. The laboratory assistants at the Oil and Gas Vocational School have limitations in explaining in detail about drilling fluids. Therefore, activity is necessary to increase insight and knowledge of drilling fluids, especially in supporting practical activities. The method used in this activity is the dissemination of knowledge about drilling mud accompanied by the practice of making a simple drilling mud mixture. Making drilling mud is carried out by comparing KCl polymer mud and polyamine as a shale inhibitor. This comparison is seen from the results of the physical properties of the mud produced, namely mud weight, funnel viscosity, plastic viscosity, yield point, 10-second gel strength, 10-minute gel strength, filtration rate, mud cake, and pH (acidity level). With this introductory activity, knowledge about drilling fluids for laboratory assistants and chemistry teachers as participants in PkM activities has increased. This increase in knowledge can benefit students who will continue their education at the undergraduate level in earth sciences at universities.